Role of methods for car-repairing organizations and their influence on increase of labor efficiency - Myamlin, V. V. (Science and Transport Progress, 2011)
The advantages of the line form of production organization are shown. The examples of forming the lines in different branches of industry are given. Main characteristics of line production are presented. An important role in the development of new structures of car repair lines promoting in production efficiency and labor productivity growth is emphasized. Huge reserves in this direction can be seen in creation of multi-subject flexible asynchronous systems with high level of production mechanization and automation.